The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1002/ppsc.201600115
|View full text |Cite
|
Sign up to set email alerts
|

Ge Nanoparticles Encapsulated in Interconnected Hollow Carbon Boxes as Anodes for Sodium Ion and Lithium Ion Batteries with Enhanced Electrochemical Performance

Abstract: A carbothermal reaction route to Ge nanoparticle homogeneously encapsulated hollow carbon boxes from NH4H3Ge2O6/resorcinol formaldehyde precursors is designed, using NH4H3Ge2O6 as a Ge precursor from commercial GeO2 and NH4OH. The Ge/C hybrid anode for sodium ion battery displays a higher Na+ storage capacity of 346 mA h g−1 after 500 cycles at a current density of 100 mA h g−1, almost approaching the theoretical capacity of Ge. Furthermore, Ge/C anode shows significantly improved electrochemical performance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 42 publications
(104 reference statements)
0
18
0
Order By: Relevance
“…Nevertheless, in situ TEM [ 143 ] results confirmed that crystalline Ge do not sodiate, while amorphization can make the Ge an effective sodiation electrode, in which the observed volume expansion is more than 300% than expected based on final sodiated phase close to Na 1.6 Ge. Ge nanoparticles homogeneously encapsulated in hollow carbon boxes [ 144 ] is designed to show a high Na + storage capacity of 346 mAh g −1 after 500 cycles at 0.1 A g −1 ( Figure a). The internal void space of hollow carbon boxes can buffer the volume change of Ge during sodiation process, preserving structural stability of anode materials.…”
Section: Alloying‐based Anode Materials In Sibs/pibsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in situ TEM [ 143 ] results confirmed that crystalline Ge do not sodiate, while amorphization can make the Ge an effective sodiation electrode, in which the observed volume expansion is more than 300% than expected based on final sodiated phase close to Na 1.6 Ge. Ge nanoparticles homogeneously encapsulated in hollow carbon boxes [ 144 ] is designed to show a high Na + storage capacity of 346 mAh g −1 after 500 cycles at 0.1 A g −1 ( Figure a). The internal void space of hollow carbon boxes can buffer the volume change of Ge during sodiation process, preserving structural stability of anode materials.…”
Section: Alloying‐based Anode Materials In Sibs/pibsmentioning
confidence: 99%
“…Ether-based electrolyte [179] can provide more stable interface, Figure 15. The relationship between reversible capacity and cycle number for typical reported alloy-based anode for SIBs [8,18,29,39,40,[87][88][89]106,122,128,144,152,154,156,158,166,168] and PIBs. [64,100,101,130,161] The inset image: main research process changes for alloy-based anode.…”
Section: Summary Of Performance and Research Processmentioning
confidence: 99%
“…Among the group 14 elements (Si, Ge, and Sn), Ge comes into the sights of the researchers could be due to multiple reasons: 1) Ge shows strong thermodynamic tendency to alloy with Na + (comparable to Sn and stronger than Si), 2) moderate volume expansion and bulk modulus (lower than Sn), and 3) faster Na + conductivity (comparable to Sn). Li et al have successfully synthesized Ge nanoparticles that are encapsulated in interconnected hollow carbon boxes via a carbothermal reducing route ( Figure a–c) . A specific capacity that is approaching the theoretical value of Ge (346 mAh g −1 ) is maintained at 100 mA g −1 after 500 cycles.…”
Section: Alloy Anodes For Sibsmentioning
confidence: 99%
“…a) SEM and b,c) TEM images of the Ge nanoparticle encapsulated in hollow carbon box. Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Alloy Anodes For Sibsmentioning
confidence: 99%
“…[ 16–19 ] Among various alloy‐type materials, Ge has been found to electrochemically react with Na to form Na x Ge (369 mAh g −1 ) with an atomic ratio of about 1:1. [ 20,21 ] However, bulk Ge is undesirable for sodium storage because of the sluggish kinetics. [ 22 ] Besides, the alloying reactions are usually accompanied by huge volume expansion of the host materials, which leads to anode degradation and poor capacity retention.…”
Section: Figurementioning
confidence: 99%